L’emergenza sanitaria e l’impatto sul (già) difficile equilibrio tra sfera lavorativa e sfera privata (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
The essay examines the impact of the legislative measures enacted in Italy to face the health emergency on work conditions. In the regime of social distancing, with the concomitant closure of the schools, workers confronted with increasing difficulties in balancing private life and professional sphere. The essay focuses on the legislative response to this problem and to the consequences of this crisis on working women.
Keywords: Work-life balance; health emergency; gender equality; discrimination; smart working